True Health vs. Response Styles: Exploring Cross-country Differences in Self-reported Health - Hendrik Jürges (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
The aim of this paper is to decompose cross-national differences in self-reported general health into parts explained by differences in "true" health, measured by diagnosed conditions and measurements, and parts explained by cross-cultural differences in response styles. The data used were drawn from the Survey of Health, Ageing and Retirement in Europe 2004 (SHARE), using information from 22,000 individuals aged 50 and over from 10 European countries. Self-rated general health shows large cross-country variations. According to their self-reports, the healthiest respondents live in the Scandinavian countries and the least healthy live in Southern Europe. Counterfactual self-reported health distributions that assume identical response styles in each country show much less variation in self-reports than factual selfreports. Danish and Swedish respondents tend to largely over-rate their health (relative to the average) whereas Germans tend to under-rate their health. If differences in reporting styles are taken into account, cross-country variations in general health are reduced but not eliminated. Failing to account for differences in reporting styles may yield misleading results.
Keywords: C42; I12; 330; Self-assessed health; Response bias; Cross-national study; Gesundheit; Messung; Alte Menschen; EU-Staaten